Déficit de conocimiento en cistitis y su relación con la pielonefritis en mujeres de 20 a 40 años sexualmente activas que son atendidas en el Centro de Salud del cantón Quinsaloma, provincia de Los Ríos, durante el primer semestre del año 2014 - Guerrero López, Rosa Elvira (2015)
This document is based on the following assumptions: Urinary tract infections in women are a serious public health problem; It is estimated that half of women experience urinary at least once in their life, 80% of cystitis originate in sex infection. How it affects the knowledge deficit in relation to cystitis and pyelonephritis in women sexually active 20 to 40 years, treated at the Health Center of Canton Quinsaloma? This research is descriptive and quantitative, To obtain information, I requested observation Health Center where interviews with users aged 20 to 40 years of age was performed sexually active. According to graphic research reveals that unfortunately 62% of respondents have no knowledge about what causes cystitis, while the lowest percentage of 38% considered to know the subject. It was concluded that the increased incidence of vaginitis in women is mostly presented by no knowledge of the causes and complications of cystitis. Although most vaginal infections in women are due to bacterial vaginosis, trichomoniasis, or yeast, there are other causes. Keywords: Knowledge, Sexual Relations, recurrent